Presence of a trs-like motif promotes rep-mediated wild-type adeno-associated virus type 2 integration - Petri, Karl; Gabriel, Richard; Fronza, Raffaele; Afzal, Saira; Käppel, Christine; Schmidt, Manfred (Journal of virology, 2015)
High-throughput integration site (IS) analysis of wild-type adeno-associated virus type 2 (wtAAV2) in human dermal fibroblasts (HDFs) and HeLa cells revealed that juxtaposition of a Rep binding site (RBS) and terminal resolution site (trs)-like motif leads to a 4-fold-increased probability of wtAAV integration. Electrophoretic mobility shift assays (EMSAs) confirmed binding of Rep to off-target RBSs. For the first time, we show Rep protein off-target nicking activity, highlighting the importance of the nicking substrate for Rep-mediated integration.